2020
DOI: 10.3390/molecules25092081
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Rich Products from Aphloia theiformis (Vahl) Benn Leaves: Extraction, Fractionation, Phytochemical Characterization, and Antioxidant Properties

Abstract: Aphloia theiformis is traditionally used in Mauritius, Madagascar, and Reunion Island for treating several diseases. In this study, various extraction solvents and schemes were applied for the recovery of antioxidant rich fractions from the leaves of A. theiformis. The products were evaluated for their antioxidant capacity using well known in vitro assays. Major compounds were characterized by UPLC–QTOF–MS. Hydrophilic extracts of A. theiformis demonstrated strong antioxidant properties, which are comparable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This process splits the higher quantities of bioactive compounds from the complex mixtures, which could be applied to separate the target compounds. This is an important step in bio-guided assays of new phytochemical ingredients [ 32 ]. Chua et al [ 33 ] reported that highly polar substances, such as organic acids, polysaccharides, and proteins, might remain in the aqueous phase, while the other less polar compounds, including terpenoids, could be segregated into the organic phase.…”
Section: Discussionmentioning
confidence: 99%
“…This process splits the higher quantities of bioactive compounds from the complex mixtures, which could be applied to separate the target compounds. This is an important step in bio-guided assays of new phytochemical ingredients [ 32 ]. Chua et al [ 33 ] reported that highly polar substances, such as organic acids, polysaccharides, and proteins, might remain in the aqueous phase, while the other less polar compounds, including terpenoids, could be segregated into the organic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Aquilaria leaf was subjected to mangiferin extraction using ultrahigh-performance liquid chromatography (UHPLC) coupled with electrospray ionization (ESI) tandem mass spectrometry (MS/MS) method [18]. Mangiferin was also extracted from Aphloia theiformis using liquid-liquid extraction followed by UPLC-QTOF-MS [19].…”
Section: Mangiferin: Natural Sources and Extraction Methodsmentioning
confidence: 99%